Challenges in rural maternal health: how received public services and policy awareness affect health knowledge and practices - Yang, Jie; Chen, Jun; Xie, Yuyang; Liu, Yunjie; Wu, Junhao; Li, Yangyuan; Nie, Jingchun (Frontiers in Public Health, 2025)
PurposeThis study evaluates the effectiveness of rural maternal health services in improving pregnant women’s health knowledge, practices, and outcomes in northwestern China, focusing on the roles of received public services and policy awareness.MethodsBaseline surveys were conducted in rural Shaanxi Province in 2021 and 2023, involving 1,152 pregnant women from 85 townships, selected via multistage cluster random sampling. Data were collected through structured face-to-face interviews, covering health knowledge and behaviors. Statistical analyses were performed to assess the impact of maternal health services.ResultsBoth received public services (Coefficient: 0.130, 95% CI: 0.015–0.246) and policy awareness (Coefficient: 0.114, 95% CI: 0.001–0.227) significantly improved nutrition and health knowledge but had limited impact on prenatal checkups or health outcomes. Policy awareness (OR: 3.826, 95% CI: 2.743–5.337) significantly increased picking up free folic acid, however, the rate of taking folic acid remained low.ConclusionWhile received public services and policy awareness improved nutrition and health knowledge, and policy awareness increased picking up free folic acid, they did not significantly influence prenatal checkups or health outcomes. More targeted efforts are needed to foster consistent health practices and improve maternal health outcomes in rural areas.